Ripley's Believe It or Not! - Ripley, Robert L. (London Ripley Publishing, 2012)
Following hot on the heels of last year's best-selling edition, "Ripley's Believe It or Not! 2012" offers an entirely new compendium of bizarre facts and features in a stunning new design, including a section on the wacky and amazing feats of the Olympic games past and present, and an 8-page pull-out featuring Ripley's first ever odditorium, which opened in 1933. For the legions of dedicated Ripley's fans, and anyone else on the planet who loves unbelievable facts and jaw-dropping images, the latest annual in the bestselling series is a feast of delights. Meet the man who chews molten lead, the cat that can predict death, the vending machine that dispenses live crabs and the artist who paints portraits with burger grease. Intriguing interviews with some of the astounding individuals who feature in the book spotlight their achievements and reveal their motivations, and informative 'Ripley's Research' boxes give the scientific explanation behind some of the most incredible tales, such as how people have turned their fingers into magnets.
Include Colored Illustrations
Keywords: Curiosities and wonders